MANAJEMEN SISTEM PENGOLAHAN DATA PERSONALIA DAN PENGGAJIAN PADA CV KAP SEMARANG - Hendri Rasminto; Muhamad Sidik (Jurnal Publikasi Manajemen Informatika, 2025)
CV KAP Semarang is a company is engaged in Manpower Providers, the employee data management system and salary calculation at CV KAP Semarang , is still carried out in the conventional way, namely bookkeeping is carried out every 25th of every month taken from each worker, then the company makes billing to each user or outsourcing service user on the 1st to 10th every month, there are weaknesses or obstacles to the system, namely: Often there is a data discrepancy, which is obtained by the finance department from the personnel section of the user, so that the salary calculation process in the financial section is long delays in data input and can also result in incorrect salary calculations .. With a manual system or it takes a long time and is inefficient because you have to wait about 10 days or 1 week to wait for the data input process to calculate the salary. The process of reporting to the leadership also experienced delays because of the delay in the process.